Women Obsession To Get Children In Susan Elizabeth Phillips'Nobody's Baby But Mine Novel (1998): A Psychoanalytic Approach - Setyawati, Sulis; , Drs. Abdillah Nugroho, M.Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
The problem of this study is women obsession to get children in Susan Elizabeth Phillips' Nobody Baby but Mine novel. The objective of this study is to analyze the novel based on the structural elements and to analyze the novel based on the psychoanalytic approach. The type of this research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is nobody Baby but Mine novel written by Susan Elizabeth Phillips' in 1998. While the secondary data sources are other materials taken from author's biography, essay, comments, critics and internet related to the study. Both data are collected by conducting library research and analyzed by descriptive analysis. Based on the analysis, the writer portrays some conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, setting, plot, point of view, theme, are supporting each other to produce a good quality novel . Second, based on the psychoanalytic analysis, the study shows that the problem faced by the major character is his own psychology condition to decide the appropriate ways for his life. This novel also shows the process that conviction for success with the power of Loves.